Effects of pH, Nacl and Teating on the Antibacterial Stability of Kecombrang - Rifda Naufalin; Betty Sri Laksmi Jenie; Feri Kusnandar; Mirnawati Sudarwanto; Herastuti Sri Rukmini (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2006)
The effect of pH (4-9), NaCl concentration (1-5%), temperature and heating time (80, 100 and 1210C for 10, 20 and 30 minute) on the antibacterial effectivity of ethyl acetate and ethanol kecombrang extract were analysed. Both ethyl acetate and ethanol extracts showed antibacterial activity at pH 4-8, but its activity gradually decreased at higher pH. At pH 9, only ethanol extract still showed antibacterial activity. Addition of 1-4% NaCl on ethyl acetate and ethanol extract still showed antibacterial activity. Heating the extracts at 80-100 0C for 10-30 minutes and 1210C for 10 minutes did not haves significantly affect on the antibacterial activity of both ethyl acetate and ethanol extracts. Application of ethyl acetate extract at the concentration of 1 and 3 MIC on minced meat were still effective to reduce the viable bacteria until 7 days and 5 MIC was still effective until 9 days. Key words : Kecombrang, pH, NaCl, temperature and heating time, antibacteria